Determinan Kepuasan Pasien pada Pelayanan Rawat Inap di Rumah Sakit : Systematic Literature Review - Basir, Hasmira; Wahyono, Bambang (Jurnal Kesehatan Mahardika, 2023)
There was an increase in hospital development of 3.02% and the patient satisfaction index for services in Indonesia has not yet reached the minimum standard of above 95%. The research was conducted aiming to identify the determinants of patient satisfaction in inpatient services at the hospital with a systematic literature review method. Findings were selected using the PRISMA method and article searches obtained through Google Scholar, Portal Garuda and DOAJ until 18 articles were identified that were worthy of review in the research. Based on the findings, the determinants that affect patient satisfaction are age, gender, education, income, occupation, environment, facilities, length of hospitalization, doctor's service, nurse's service and quality of health service. Based on analysis of 18 articles that met the inclusion criteria, it can be concluded that the determinants of age, gender, education, occuption, income, environment, facilities, length of stay, doctor’s services, nurse’s services and quality of health services affect patient satisfaction in inpatient services at the hospital.